2007
DOI: 10.1016/j.jvs.2006.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Gender-associated differences in plaque phenotype of patients undergoing carotid endarterectomy

Abstract: Carotid artery plaques obtained from women have a more stable, less inflammatory phenotype compared with men, independent of clinical presentation and cardiovascular risk profile. Asymptomatic women demonstrate the highest prevalence of stable plaques. These findings could explain why women benefit less from carotid endarterectomy compared with men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
131
3
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(154 citation statements)
references
References 37 publications
17
131
3
3
Order By: Relevance
“…5 The stability of the atherosclerotic plaque may be one of the factors that explain these findings. In line with previous observations showing a more unstable plaque phenotype in men, 6 we observed that PH in the atherosclerotic plaque is more prevalent in men with carotid artery stenosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…5 The stability of the atherosclerotic plaque may be one of the factors that explain these findings. In line with previous observations showing a more unstable plaque phenotype in men, 6 we observed that PH in the atherosclerotic plaque is more prevalent in men with carotid artery stenosis.…”
Section: Discussionsupporting
confidence: 93%
“…[1][2][3][4][5] One of the possible factors contributing to this sex-associated difference is carotid plaque phenotype, which is significantly more stable in women, especially in asymptomatic patients. 6 Plaque hemorrhage (PH) may lead to accelerated progression of atherosclerotic disease. The leakage of erythrocytes and leukocytes into the atherosclerotic plaque results in an accumulation of atherogenic factors, such as cholesterol, macrophages, and iron, which can contribute to plaque instability.…”
mentioning
confidence: 99%
“…Hellings et al carefully analysed histomorphological and inflammatory parameters from intraoperatively removed plaques regarding gender differences. This study reports that plaques in women show higher smooth muscle cell content, contain less fat and are less inflamed, as concluded from lower IL-8 concentration, lower MMP8 activity and lower macrophage content [15]. Clearly, plaques in women are generally more stable than in men.…”
Section: Analysis Of Plaque Morphologymentioning
confidence: 60%
“…The gender-associated differences in plaque morphology are most evident in women with asymptomatic carotid artery stenosis, which may explain why they in particular have lower long-term stroke reduction after CEA [11][12][13][14][15].…”
Section: Analysis Of Plaque Morphologymentioning
confidence: 99%
“…Similarly, Hellings et al evaluated 450 patients undergoing CEA, and demonstrated that men had higher rates of unstable plaque with more inflammatory features, for example, higher concentration of fat, higher number of macrophages and higher levels of IL-8 and matrix metalloproteinase (MMP)-8 activity [32]. This was regardless of the types of symptoms attributed to the carotid (amaurosis fugax, hemispheric transient ischemic attack or ischemic stroke) or the cardiovascular risk profile [32].…”
Section: Sex Differences In Intermediate Outcomes Of Stroke: Carotid mentioning
confidence: 99%